Forms of Expression of the Author’s Consciousness in Contemporary Russian Drama - Журчева, Ольга (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The article is devoted to the problem of authorial intention in contemporary Russian drama. Firstly, major theoretical approaches to the ‘problem of the author’ in drama are identified. It is then demonstrated how cultural paradigms change in an artistic consciousness and how, as a consequence, the most important structural components of drama – conflict, character, genre – become discredited and deconstructed. There follows an overview of specific examples of such transformations of these generic features of drama. It is argued in the paper that such transformations result from the activation of the author’s consciousness and are a manifestation of the author’s intentions regarding the modern picture of the world.